Metabolic diversity in sweet potato (Ipomoea batatas, Lam.) leaves and storage roots - Margit Drapal; Genoveva Rossel; Bettina Heider; Paul D. Fraser (Horticulture Research, 2019)
Food crops: Assessing the metabolic diversity of sweet potato Understanding the metabolic variations of different types of sweet potato could help improve their nutritional value. Sweet potato is one of the world’s major food crops but recurrent breeding of high yielding lines is reducing their genetic diversity. A study led by Paul D. Fraser, Royal Holloway University of London, UK, examined the chemical differences between 25 types of sweet potato, including orange and purple varieties. They show that there is little correlation between the chemicals found in the leaves and storage root material and that there are significant differences in metabolism between varieties that produce different pigments in their storage roots. Their findings highlight the importance of metabolite profiling for identifying those varieties that produce the highest levels of starch and health-promoting compounds such as carotenoids.